Working to improve the management of sarcoma patients across Europe: a policy checklist - Kasper, Bernd (BMC cancer, 2018)
The Sarcoma Policy Checklist was created by a multidisciplinary expert group to provide policymakers with priority areas to improve care for sarcoma patients.